An Active and Popular Facebook Page Equals Better Chances of Winning an Election? The 2013 Malaysian General Election Case - Adib Khairuddin, Mohammad; Rizal Mohd Isa, Mohd; Maskat, Kamaruzaman; ‘Afizi Mohd Shukran, Mohd; Nazri Ismail, Mohd; Fahmi Mohamad Amran, Mohd; Naim Abdullah, Muhammad; ., . (International Journal of Engineering and Technology, 2018)
Social media is becoming a significant platform for election campaigning allowing for both communication and interaction between candidates and the public. However, most research points to social media being used mainly for broadcasting of information, and there is a need to test whether the interactive features are being used and are influencing election results. With the ability of researchers to download and collect masses of raw data from various social media such as Twitter and Facebook, the research into social media is now becoming more quantitative. With traditional media completely owned and controlled by the government, while the internet is free and uncensored, the use of social media in Malaysia has exploded over the past few years, with a corresponding use of this medium in campaigning, leading to researches attributing this to the rise of a viable opposition. In this paper we study passive interaction using data captured directly from the 2013 Malaysian General Election candidatesâ€™ Facebook Pages (FP), and show that the success of a candidate who is active and popular on Facebook rises to 77% when compared to the 38% general success rate of all candidates.Â Keywords:Â Social media is becoming a significant platform for election campaigning allowing for both communication and interaction between candidates and the public. However, most research points to social media being used mainly for broadcasting of information, and there is a need to test whether the interactive features are being used and are influencing election results. With the ability of researchers to download and collect masses of raw data from various social media such as Twitter and Facebook, the research into social media is now becoming more quantitative. With traditional media completely owned and controlled by the government, while the internet is free and uncensored, the use of social media in Malaysia has exploded over the past few years, with a corresponding use of this medium in campaigning, leading to researches attributing this to the rise of a viable opposition. In this paper we study passive interaction using data captured directly from the 2013 Malaysian General Election candidatesâ€™ Facebook Pages (FP), and show that the success of a candidate who is active and popular on Facebook rises to 77% when compared to the 38% general success rate of all candidates.Â Â